1998
DOI: 10.1002/(sici)1521-3765(19981102)4:11<2154::aid-chem2154>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Internal Lewis Acid Coordination as a Powerful Tool To Promote Highly Stereoselective Alkylation ofα-Alkyl-β-Hydroxy Ketones with Grignard Reagents

Abstract: An efficient and highly diastereoselective protocol is described for the alkylation of b-hydroxy ketones that contain an a-stereocenter. This method is based on the preliminary transformation of the b-hydroxy group into a titanium alcoholate by means of the facile transmetalation of the corresponding b-silyloxy derivative with TiCl 4 (Method A) or by reaction of the lithium alcoholate with TiCl 4 (Method B).On account of the strong internal coordinating action of the Lewis acid, this intermediate assumes a rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…In addition, we found that the reaction carried out with BH 3´T HF alone does not work at low temperature. Finally, the stereochemical picture shown in the reduction is quite similar to that observed for the alkylation process, [7] in which experimental evidence proved that the attack of the carbanion on the carbonyl group occurs before any interaction with titanium.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, we found that the reaction carried out with BH 3´T HF alone does not work at low temperature. Finally, the stereochemical picture shown in the reduction is quite similar to that observed for the alkylation process, [7] in which experimental evidence proved that the attack of the carbanion on the carbonyl group occurs before any interaction with titanium.…”
Section: Resultssupporting
confidence: 67%
“…[7] In particular, a solution of the hydride ion source in THF was added at À 78 8C to a b-hydroxy ketone titanium alcoholate prepared in THF by transmetallation of the corresponding lithium alcoholate with TiCl 4 . When the reduction was complete, the mixture was quenched with dilute HCl (1m).…”
Section: Resultsmentioning
confidence: 99%
“…After oxidation of the Bpin unit of 9 to an alcohol, highly diastereoselective addition of a methyl Grignard generated 46 . [24] Likewise, diastereoselective reduction of the oxidized product derived from 43 provided 47 , which could also be cyclized under copper catalysis to provide chromane derivative 48 . [25] …”
mentioning
confidence: 99%
“…Owing to the ring strain of bicyclic alkene 37 , ring‐opening cross‐metathesis with ethylene allowed for the formation of 45 . After oxidation of the Bpin unit of 9 to an alcohol, highly diastereoselective addition of a methyl Grignard generated 46 . Likewise, diastereoselective reduction of the oxidized product derived from 43 provided 47 , which could also be cyclized under copper catalysis to provide chromane derivative 48…”
Section: Methodsmentioning
confidence: 99%